Generating tumor-specific T cells based on a head and neck cancer organoid for adoptive cell therapy - Chen, Yinyu; Wang, Shoupeng; Zheng, Luxi; Chen, Lin; Xu, Feng; Guo, Shuqi; Meng, Jian (Frontiers in Immunology, 2025)
BackgroundA head and neck cancer organoid (HNCO) and peripheral blood T cell co-culture model was established to investigate whether HNCOs can induce the differentiation of peripheral blood T cells into tumor-reactive T cells. Additionally, this study seeks to explore the cytotoxicity of these T cells against autologous tumor organoids, providing theoretical and experimental evidence for the feasibility of this model as a platform for adoptive cell immunotherapy in head and neck cancer (HNC).MethodsHNCO single cells were co-cultured with peripheral blood lymphocytes (PBLs) collected and isolated from patients with HNC. The culture supernatant was collected and assayed for interferon-gamma (IFN-γ) and tumor necrosis factor-α (TNF- α). The expression of T cell activation markers cluster of differentiation (CD)137 and CD107a was measured by flow cytometry to confirm tumor specificity and cytotoxicity. Additionally, the optimal effector-to-target (E/T) ratio was determined using the Cell Counting Kit-8 assay, and HNCO killing was quantified by fluorescent labeling.ResultsOf the 27 successfully established HNCO-T cell co-culture systems, 81.48% induced the in vitro differentiation and tumor-reactive CD8+ T cell expansion capable of mediating the killing of mature HNCOs.ConclusionThe patient-derived HNCO-T cell co-culture model effectively induced PBL differentiation into tumor-reactive CD8+ T cells with enhanced tumor-killing activities. This model serves as a novel in vitro preclinical tool for advancing personalized adoptive immunotherapy in HNC.